Fuertemayo F2016: variety of bread wheat for irrigated sowings in Mexico - Villaseñor Mir, Héctor Eduardo; Huerta Espino, Julio; Santa Rosa, René Hortelano; Solís Moya, Ernesto; Alvarado Padilla, Jorge Iván; Martínez Cruz, Eliel (Revista Mexicana de Ciencias Agrícolas, 2023)
In Mexico, the main wheat-producing regions are located in the northwest (Sinaloa, Sonora and Baja California), where 64% of national production is obtained, under irrigation conditions during the autumn-winter cycle. Fuertemayo F2016 is a spring flour wheat, released by the National Institute of Forestry, Agricultural and Livestock Research. It is of intermediate cycle, with average height of 93 cm, presents grain of medium size and white color. The line that gave rise to Fuertemayo F2016 was generated by the International Maize and Wheat Improvement Center and was evaluated by the National Institute of Forestry, Agricultural and Livestock Research in 60 environments of normal and limited irrigation. The yield under normal irrigation was 4 999 kg ha-1 and under limited irrigation was 4 576 kg ha-1, surpassing the controls by 3% (Roelfs F2007) up to 28% (Palmerín F2004). Its greatest advantage over the controls is its resistance to leaf and yellow rust, the maximum level of severity was 5 to 20%, respectively. It possesses the resistance genes of pleiotropic effect Lr46/Yr29/Sr58, Sr2/Yr30 and Lr68. It is a semi-hard grain variety, with average hectoliter weight of 79 kg hl-1 and average protein content in flour of 11.7%. For its W= 350 x 10-4 J, it is classified as having strong gluten, suitable for the mechanized baking industry and can be mixed to improve weak dough flours. It is recommended for sowings under normal and limited irrigation during the winter, in early to late dates in the states of Sinaloa, Baja California, Chihuahua, Coahuila, Nuevo León, Tamaulipas, and in early to intermediate dates in the region of El Bajío.
Keywords: quality; resistance; yield